If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 = 6 + 2x Reorder the terms: -3 + 2x = 6 + 2x Add '-2x' to each side of the equation. -3 + 2x + -2x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + 0 = 6 + 2x + -2x -3 = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 = 6 + 0 -3 = 6 Solving -3 = 6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -80.2-9x=1.7 | | 10x-75=51+4x | | o=5-(2x-17) | | x+3.07+2.5=1.8 | | -80.2-9x=-21.9 | | 10a+55b= | | 3x+7-9x=-11 | | x+43=87 | | x+5=1.5x+2.5 | | 10f+2(5f+8)=-10f-4(2f-30) | | 5d+9=24 | | 2=17 | | 8ex=7 | | p*(q+r)=qp+pr | | y^2+9xy+18x^2=0 | | 32860-0.06x=x | | 7y+5=6y | | -43+11x=6x+32 | | -2k-16=3h-6 | | 2(x+4)=12x+62 | | 46=-6-8 | | 269.50=14 | | X-.4x=60 | | 20x+10y=0 | | 19-11n+16n-4= | | 9u^2+1u-10=0 | | X-x(.4)=60 | | 20x+10y=107 | | 3x+10=6x-19 | | 3z+1=34 | | -42-10x=53-5x | | 6x+9=4(-x) |